Prevalence, Antibiotic Resistance, and Genetic Diversities of Clostridium difficile in Meat Nuggets from Various Sources in Isfahan, Iran - Parvin Ghorbani Filabadi; Ebrahim Rahimi; Amir Shakerian; Zahra Esfandiari (Journal of Food Quality)
Clostridium difficile is recognized as one of the leading causes of diarrhea and is responsible for almost all cases of pseudomembranous colitis. The main aim of this study was to determine the prevalence and genetic diversities of Clostridium difficile contamination in meat nuggets in Isfahan (Iran). To achieve this, 100 samples of chicken, ostrich, quail, shrimp, fish, and beef nuggets were collected by the simple random sampling method from the market of Isfahan from July 2018 to July 2019. Microbiological analyses were performed on each collected sample to isolate and identify C. difficile strains. Susceptibility of the isolated strains to antibiotics was assessed by the Kirby–Bauer method. The PCR technique was used to identify the genes responsible for producing toxins. Of the 600 food samples, 7 C. difficile strains were found, representing a prevalence of 1.17%. Based on the obtained antibiogram results, the highest resistance was related to ampicillin (100%) and then amoxicillin (85.72%), and the highest susceptibility was related to vancomycin (100%) and metronidazole (85.72%). Concerning the identification of the genes responsible for the production of the toxins, it appears that que 4 samples (57.14%) had tcdA genes, 2 samples (14.57%) had tcdC genes, and 7 samples (100%) had tcdB genes. The cdtA and cdtB genes were observed in only one positive sample on beef. This study showed the presence of C. difficile in the analyzed food products. The isolated strains are toxigenic and resistant to antibiotics, except for vancomycin. A mutation would be the basis for the absence of the tcdC gene in the genome of all isolates.